Analisis Implementasi Kebijakan Pembinaan Teritorial TNI AD untuk Pencegahan Konflik Sosial di KODIM 0618/Kota Bandung - Fitrianang, Very Grahita; Soeling, Pantius Drahen (Jurnal Administrasi dan Kebijakan Publik, 2024)
The implementation of the Indonesian Army (TNI - AD) Territorial Development Policy is based on the policy implementation process approach which has several dimensions, namely size and objectives, resources, characteristics of implementing agencies, communication, disposition, social, economic and political environment. This research uses a post-positivism paradigm with qualitative methods. The data collection techniques used are in-depth interviews and document studies. The result is the Implementation of the Army Territorial Development Policy for the prevention of social conflict in Kodim 0618 / Bandung City, the researcher concluded that the implementation of the policy has not been carried out optimally because it has experienced several obstacles. Lack of clear information about territorial development to the TNI and the community, information that is not clear enough can complicate understanding of territorial development. The obstacle in the implementation can be caused by the low human resource factor.